Avicenna's Canon of Medicine and Modern Urology. Part IV: Normal Voiding, Dysuria, and Oliguria - Madineh, Seyed Mohammad Ali (Urology Journal, 2009)
Avicenna, the Iranian scientist, describes the mechanisms of normal voiding in his famous book, the Canon of Medicine. Then, he enumerates urinary symptoms. In this article, his discussion on dysuria, its causes, and its pathophysiology is compared with these concepts in modern urology. Avicenna points to some etiologic theories of interstitial cystitis and chronic prostatitis. In the Canon, we can distinguish bases of the theory of infection and mucosal theory, along with abnormalities of urine, psychological factors, and abnormalities in prostatic secretions. Avicenna also indicates some differential diagnoses of and associated disorders with interstitial cystitis. His short but rather concise discussion on oliguria and its causes is an interesting point for urologists and nephrologists.